Peluang Bisnis melalui Peningkatan Pengetahuan dan Kreativitas Pembuatan Batik Gutta - Ida, Ida; Yulianti, Diana Trivena; Tan, Indra Janty; Aryani, Dewi Isma (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Batik as a cultural heritage of the Indonesian nation has high aesthetic value and economic potential. Limited knowledge regarding batik techniques with gutta and restricted access to non-formal education that teaches practical skills among the women’s congregants of the Gereja Utusan Pantekosta is a problem in empowering women to use their free time productively as a business opportunity that can improve family welfare. The empowerment of women’s congregants of the Gereja Utusan Pantekosta through batik-making training using the gutta technique to enhance practical skills that are easy to learn and apply was conducted on March 23, 2024. This initiative was a collaboration between the Faculty of Digital and Law Business, the Faculty of Humanities and Creative Industries, and the Faculty of Intelligent Technology and Engineering at Maranatha Christian University, along with Universitas Komputer Indonesia and the industrial partner Istana Kaen. The training involved 21 participants aged between 19 and 66 years. The implementation method included explanations, demonstrations, practical sessions, and mentoring. Participants gained increased knowledge and could create batik designs after the training.